Studies on Corrosion of Metals in Surat Urban Environment - Vashi, R.T.; Patel, R.N.; Contractor, K.S.; Desai, S.A. (Asian Journal of Chemistry, 2010)
Corrosion rate of mild-steel, zinc and aluminium as well as the sulphation rate and atmospheric salinity rate have been determined in 1999-2000 under outdoor exposure at Surat representing urban atmosphere. Monthly corrosion rate of mild-steel, zinc and aluminium vary from 270 to 1050 (47 to 182 μm/y), 17 to 59 (3 to 10 μm/y) and 5 to 16 (2 to 7 μm/y) mg/dm2 respectively; whereas yearly corrosion rate being 1196 to 3205 (17 to 46 μm/y), 41 to 115 (0.6 to 1.6 μm/y) and 27 to 52 (1 to 2 μm/y) mg/dm2 for mild-steel, zinc and aluminium, respectively. A sulphation rate was measured and was found in the range of 13 to 29 mg.SO3/dm2/month. Atmospheric corrosion rate of mild-steel indicates a close correlation with rainfall (r = 0.86) and number of rainy days (r = 0.88).